1995
DOI: 10.1001/archpsyc.1995.03950220039008
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Excitatory Neurotransmitter Metabolism in Schizophrenic Brains

Abstract: The changes in levels of aspartate, glutamate, NAAG, and NAALADase are prominent in the prefrontal and hippocampal regions, where previous neuropathological studies of schizophrenic brains demonstrate consistent changes. These findings support the hypothesis that schizophrenia results from a hypofunction of certain glutamatergic neuronal systems. They also suggest that the therapeutic efficacy of neuroleptics may be related to increased glutamatergic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
166
4
8

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(196 citation statements)
references
References 40 publications
17
166
4
8
Order By: Relevance
“…Interestingly, Tsai et al (1995) described increased levels of N-acetylaspartylglutamate (NAAG) in schizophrenic brains. This observation is particularly relevant to the present study, as NAAG is an agonist at mGlu3 receptors (Wroblewska et al, 1997(Wroblewska et al, , 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Tsai et al (1995) described increased levels of N-acetylaspartylglutamate (NAAG) in schizophrenic brains. This observation is particularly relevant to the present study, as NAAG is an agonist at mGlu3 receptors (Wroblewska et al, 1997(Wroblewska et al, , 1998.…”
Section: Discussionmentioning
confidence: 99%
“…A hypofunction of the glutamatergic system and NMDA receptors has been hypothesized in schizophrenia (for review, see Olney and Farber 1995) and appears to be supported by post-mortem studies (Nishikawa et al 1983;Toru et al 1988;Ishimaru et al 1994;Tsai et al 1995). If schizophrenic symptoms are the result of the diminished functioning of NMDA receptors, stimulation of these receptors could be beneficial for patients with schizophrenia.…”
mentioning
confidence: 93%
“…2 healthy subjects and exacerbate such symptoms in patients with schizophrenia (Luby et al 1962;Javitt and Zukin 1991;Krystal et al 1994;Lahti et al 1995;Malhotra et al 1997b). A hypofunction of the glutamatergic system and NMDA receptors has been hypothesized in schizophrenia (for review, see Olney and Farber 1995) and appears to be supported by post-mortem studies (Nishikawa et al 1983;Toru et al 1988;Ishimaru et al 1994;Tsai et al 1995).…”
mentioning
confidence: 98%
“…Proton magnetic resonance spectroscopy ( 1 H MRS) poses an unprecedented opportunity for noninvasive assessment of brain metabolism in well-defined brain areas. N-acetylaspartate (NAA), an amino acid synthesized primarily in neurons (Simmons et al, 1991) and detectable by MRS, can be used as an indirect measure of neuron functionality (Sager et al, 2001;Tsai et al, 1995). Moreover, mature oligodentrocytes can express NAA in vitro (Bhakoo and Pearce, 2000) and it was suggested that glia cells are also involved in NAA/NAAG metabolism.…”
Section: Introductionmentioning
confidence: 99%